[PP.03.13] HEART RATE VARIABILITY IN ELDERLY HYPERTENSIVE PATIENTS UNDERGOING CORONARY STENTING ON THE BACKGROUND OF ACUTE CORONARY SYNDROME. (September 2017) - Esina, O.; Esin, S.; Nosov, V.; Koroleva, L.; Tarlovskaya, E.
Abstract : Objective: To evaluate heart rate variability (HRV) in elderly patients with systolic-diastolic arterial hypertension (AH) after acute coronary syndrome (ACS), undergone coronary angioplasty and stenting. Design and method: The study included 65 elderly patients (mean age - 68, 9 ± 6, 3 years, men - 38 (58.5%)) with systolic-diastolic AH 1–3 degree and developed ACS requested a coronary angioplasty and stenting during the first 6 hours after the onset of chest pain. ACS with ST-segment elevation was observed in 35 (53.8%) patients, and ACS without ST elevation - 30 (46.2%). Patients received on the background of the use of anticoagulants and antiplatelet agents also a standard anti-ischemic and antihypertensive therapy. All patients in the hospital stage after coronary stenting performed 24 h ECG monitoring with the assessment of HRV. Results: All patients showed positive dynamics in the form of the disappearance of the chest pain, the most of them reached the target blood pressure values. The time-depend analysis had no differences between patients with ST-segment elevation, and without it, showing a decline of HRV in both groups (65, 71% vs 76, 67%). In contrast, the spectral analysis of HRV in patients with ST-segment elevation showed a statistically significant effect of the predominance of parasympathetic autonomic nervous system (HF = 40, 3 ± 14, 0% vs 34, 0 ± 14, 0%, p = 0.048; LF / HF = 1, 1 ± 1, 0 c.u.. vs 1, 4 ± 1, 2, p = 0, 048). ACS without ST-segment elevation was accompanied by a significant prevalence of the power of very low frequency waves (VLF = 33, 0 ± 16, 2% vs 26, 3 ± 13, 1%, p = 0, 032), which indicates to a high role of humoral-metabolic mechanisms of the heart rate regulation. Conclusions: The predominance of low HRV in early hospital period, even during the adequate conservative therapy, was found in elderly patients with systolic-diastolic AH after coronary angioplasty with stenting due to the ACS. ACS without ST-segment elevation was accompanied by a significant predominance of humoral-metabolic effects on HRV, it requires an intensification of the therapy with angiotensin-converting enzyme inhibitors / angiotensin receptor blockers in these patients, which based on blood pressure values.